2011
DOI: 10.4028/www.scientific.net/ssp.170.259
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Direct Synthesis of Mg<sub>2</sub>FeH<sub>6</sub> from the Elements by Reactive Milling

Abstract: Magnesium complex hydrides as Mg2FeH6 are interesting phases for hydrogen storage in the solid state, mainly due to its high gravimetric and volumetric densities of H2. However, the synthesis of this hydride is not trivial because the intermetallic phase Mg2Fe does not exist and Mg and Fe are virtually immiscible under equilibrium conditions. In this study, we have systematically studied the influence of the most important processing parameters in reactive milling under hydrogen (RM) for Mg2FeH6 synthesis: mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The synthesis of Mg 2 FeH 6 by ball milling has been studied by several authors using different milling parameters, such as: type of mill; ball to powder ratio; number and size of balls; milling time; rotational speed; milling atmosphere and hydrogen pressure [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Irrespective of the milling conditions, some iron was always detected in the milled powder representing an incomplete Mg 2 FeH 6 formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of Mg 2 FeH 6 by ball milling has been studied by several authors using different milling parameters, such as: type of mill; ball to powder ratio; number and size of balls; milling time; rotational speed; milling atmosphere and hydrogen pressure [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Irrespective of the milling conditions, some iron was always detected in the milled powder representing an incomplete Mg 2 FeH 6 formation.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that Mg 2 FeH 6 is formed from the metallic elements [2,4,19,24], while others claimed that MgH 2 is the Mg 2 FeH 6 precursor [9,20,21,25,26]. Recently, we studied the transformation of phases during hydrogen absorption of a ball milled 2Mg + Fe mixture [27].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid and practically full synthesis of Mg 2 CoH 5 by RM from the metallic elements is attributed to an appropriate choice of milling parameters. As reported by Leiva et al [12,13], a high yield synthesis of the complex hydride Mg 2 FeH 6 , which belongs to the same complex hydride family as Mg 2 CoH 5 , requires high energy transfer rates during ball milling. The results obtained for Mg 2 FeH 6 [12,13] and Mg 2 CoH 5 (this study) are supported by the model proposed by Bab and Mendoza-Z elis [14,15] for hydride formation kinetics during RM.…”
Section: Discussionmentioning
confidence: 88%
“…Some authors suggested that Mg 2 FeH 6 is formed directly from the reaction of 2Mg+Fe+3H 2 [1,2,6,8] , while others reported that the reaction involves two steps: the first one is the formation of MgH 2 , and secondly, the reaction of magnesium hydride with Fe [5,[9][10][11] . Polanski et al 11 using in-situ synchrotron X-ray diffraction showed that MgH 2 is the Mg 2 FeH 6 precursor.…”
Section: Introductionmentioning
confidence: 99%